Magnetization Reversal in Multisegmented Nanowires: Parallel and Serial Reversal Modes - Altbir-Drullinsky, D; Allende-Prieto, S; Vargas-Ayala, N (2012)
We investigate the effect of the dipolar magnetic interaction between magnetic layers mediated by non-magnetic ones in multisegmented nanowires. Multiple symmetric and non-symmetric segments are considered. We observe that due to the dipolar interaction, the magnetization reversal can follow two possible routes, a serial, or a parallel reversal process. We show that by using asymmetrical multi-segmented wires it is possible to stop the magnetization reversal of the system at any particular point. © 2012 American Institute of Physics.